Analisis Pengaruh Kebijakan Deviden, Profitabilitas dan Ukuran Perusahaan terhadap Struktur Modal pada Perusahaan Consumer Goods yang Terdaftar di Bursa Efek Indonesia pada Periode Pengamatan 2009-2012 - Monika Nova Natalia; Kirmizi '; Al-azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to know the effect of policy deviden, profitability and size company to capital structure. This research is done at consumer goods companies listed in Indonesian Stock Exchange for period 2009-2012. The data used in this research are 20 consumer goods companies during 2009-2012 have a criteria and were analyzed descriptive statistic and multiple regression were performed to test the hypotheses.The statistical methods use in this research are simple regression and multiple regressions. The result of this research find that 45,60 % capital structure influenced by variable of policy deviden, profitability and size company, while about 54,40% capital structure influenced by other variable.The result of this research shows that only policy deviden and profitability has significant effect to capital structure, and then size company has unsignificant efect to capital structure.Keywords: Capital Structure, Policy Deviden, Profitability and Size Company